The Effectiveness of Audiovisual Education on the Level of Pre-Elderly's Knowledge about Healthy Lifestyle and Hypertension Prevention - Rusni Masnina; Fitri Kholisah; Gusnawati Sulaeman; Milkhatun Milkhatun; Ghozali Ghozali (Ahmar Metastasis Health Journal, 2026)
As humans age, there are physiological changes that reduce the elasticity of blood vessel walls, which can cause increased blood pressure. In addition, unhealthy lifestyles can also cause high blood pressure. For example, lack of physical activity, stress, and poor eating habits are factors that increase the incidence of high blood pressure. Individuals aged 45-59 years (pre-elderly) need to prepare themselves to carry out self-care in order to face the emergence of hypertension. This study aims to analyze the effectiveness of audiovisual education on the level of knowledge of pre-elderly about healthy lifestyle to prevent hypertension. The research design One-group Pretest-posttest was conducted on 30 pre-elderly respondents in Samarinda City. Data collection on respondent characteristics and level of knowledge about lifestyle used a structured questionnaire. The results showed that the characteristics of pre-elderly respondents based on an average age of 52 years, while the average systolic blood pressure was 131.07 mmHg and diastolic was 84.07 mmHg. The results of statistical analysis showed that there was significant difference in the average knowledge score of respondents between before being given education (6.27) and after being given audiovisual education (7.60). The statistical test results using the Wilcoxon Signed Rank Test obtained a p-value of 0.001 (<0.05). This indicates that audiovisual education can effectively increase pre-elderly knowledge about healthy lifestyle to prevent hypertension.